Numerical investigation and dynamical analysis of mixed convection in a vented cavity with pulsating flow - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2014)
In the present study, numerical investigation of pulsating mixed convection in a multiple vented cavity is carried out for the range of parameters; Reynolds number (500 <= Re <=, 2000), Grashof number (10(4) <= Gr <= 10(6)), Strouhal number (0 <= St <= 2). The governing equations are solved with a general purpose finite volume based solver. The effects of various parameters on the fluid flow and heat transfer characteristics are numerically studied. It is observed that the flow field and heat transfer rate are influenced by the variations of Reynolds, Grashof and Strouhal numbers. Furthermore, recurrence plot analysis is applied for the analysis of the time series (spatial averaged Nusselt number along the vertical wall of the cavity) and for a combination of different parameters, the systems are identified using recurrence quantification analysis parameters including recurrence rate, laminarity, determinism, trapping time and entropy. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Mixed convection; Vented cavity; Recurrence quantification analysis; Pulsating flow